2020
DOI: 10.1002/aqc.3302
|View full text |Cite
|
Sign up to set email alerts
|

Delineating foraging grounds of a loggerhead turtle population through satellite tracking of juveniles

Abstract: 1. Tracking of juvenile sea turtles is a research priority to inform the protection of relevant habitats and ensure sustainable rates of recruitment into adult populations. Based on satellite tracking, mixed stock analysis, and mark-recapture studies, Drini Bay in the South Adriatic Sea, Central Mediterranean, has been confirmed as an important foraging site used by loggerhead turtles from all major rookeries in the Mediterranean subpopulation.2. Three juvenile loggerhead turtles (Caretta caretta) from Drini B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…However, given the zero survey effort and hence the absence of data supporting its presence in Zakynthos during the months December-May in 2016-2020, the case that this individual had already been using alternative foraging sites or even the newly detected site before 2021, cannot be excluded. Indeed, satellite tracking of two juvenile loggerheads originating from Drini Bay, Albania, (Snape et al ., 2020), over one and two years respectively, revealed that these turtles departed to distant locations during autumn/winter months only to return to Drini Bay again in April/June. In contrast, the present study provides an additional case in which (at least) seasonal residency (summer months) can also be interrupted after many years.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the zero survey effort and hence the absence of data supporting its presence in Zakynthos during the months December-May in 2016-2020, the case that this individual had already been using alternative foraging sites or even the newly detected site before 2021, cannot be excluded. Indeed, satellite tracking of two juvenile loggerheads originating from Drini Bay, Albania, (Snape et al ., 2020), over one and two years respectively, revealed that these turtles departed to distant locations during autumn/winter months only to return to Drini Bay again in April/June. In contrast, the present study provides an additional case in which (at least) seasonal residency (summer months) can also be interrupted after many years.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, loggerhead turtles recruit to neritic foraging habitats at a larger size than green turtles and continue to transition between pelagic and neritic feeding and among neritic feeding areas as juveniles (Snape et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Loggerhead turtles, in contrast, generally have a complex movement pattern during (Snape et al., 2016, 2018; Tucker, 2010) and outside of the breeding season (Dujon et al., 2018; Haywood et al., 2020 a ; Snape et al., 2016), which may make them particularly susceptible to anthropogenic activities (Lewison et al., 2014; Wallace et al., 2008). Additionally, loggerhead turtles recruit to neritic foraging habitats at a larger size than green turtles and continue to transition between pelagic and neritic feeding and among neritic feeding areas as juveniles (Snape et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We attached the transmitter to the turtle’s carapace with silicone elastomer and epoxy glue after softening the shell scales with sandpaper [ 29 ]. To observe the transmitter signal, we used the Argos system (CLS America, , accessed on 5 May 2022), which has been effectively and frequently used for sea turtle satellite tracking [ 30 , 31 , 32 , 33 ]. To increase the reliability of the tracked data, we used only coordinates with the smallest error radius on a day.…”
Section: Methodsmentioning
confidence: 99%
“…To increase the reliability of the tracked data, we used only coordinates with the smallest error radius on a day. In addition, considering the maximum speed of the sea turtles’ movement, when their movement was faster than 5 km/h (100 km/d), the data were excluded from the analysis [ 32 , 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%